On the historical role of chemical engineers in sustainability transition / Masayuki Horio - Horio, Masayuki (Universiti Teknologi MARA Shah Alam, 2019)
The chemical engineers’ historical role is defined and discussed based on the understandings on the sustainability transition, on its meaning in the human evolution, and on the present social struggle for the transition issues. First, by reviewing the history of chemical engineering, a stepwise development with roughly 30year intervals was demonstrated. Moreover, it is revealed that chemical engineering is now facing a situation where it can/must define its subject area as the whole socio-metabolic system and its target as sustainability transition. Through philosophical and sociological arguments, concepts of human existence, society and social system, production/consumption, exchange and economy, politics and policies, information, science and technology are clarified with a hope that these issues can be incorporated into chemical engineering principle in the future. By analysing the social actor structure, the significance of academic societies in the above struggle is discussed.